Staging Encystation Progression in Giardia lamblia Using Encystation-Specific Vesicle Morphology and Associating Molecular Markers - Thomas, Elizabeth B.; Sutanto, Renaldo; Johnson, Richard S.; Shih, Han-Wei; Alas, Germain C. M.; Krtková, Jana; MacCoss, Michael J.; Paredez, Alexander R. (Frontiers in Cell and Developmental Biology, 2021)
Differentiation into environmentally resistant cysts is required for transmission of the ubiquitous intestinal parasite Giardia lamblia. Encystation in Giardia requires the production, processing and transport of Cyst Wall Proteins (CWPs) in developmentally-induced, Golgi-like, Encystation Specific Vesicles (ESVs). Progress through this trafficking pathway can be followed by tracking CWP localization over time. However, there is no recognized system to distinguish the advancing stages of this process which can complete at variable rates depending on how encystation is induced. Here we propose a staging system for encysting Giardia based on the morphology of CWP1-stained ESVs. We demonstrate the molecular distinctiveness of maturing ESVs at these stages by following GlRab GTPases through encystation. Previously, we established that Giardia’s sole Rho family GTPase, GlRac, associates with ESVs and has a role in regulating their maturation and the secretion of their cargo. As a proof of principle, we delineate the relationship between GlRac and ESV stages. Through proteomic studies, we identify putative interactors of GlRac that could be used as additional ESV stage markers. This staging system provides a common descriptor of ESV maturation regardless of the source of encysting cells. Furthermore, the identified set of molecular markers for ESV stages will be a powerful tool for characterizing trafficking mutants that impair ESV maturation and morphology.